Социолингвистический аспект перевода французской литературы постмодернизма - Трибрат, О.О. (Культура народов Причерноморья, 2014)
Статья раскрывает характерные черты литературы постмодернизма, дает
характеристику сложностям, которые могут возникнуть при переводе социолингвистического аспекта
языка и причины их возникновения. Посредством сравнительного анализа перевода романа Мишеля
Уэльбека «La carte et le territorie» на русский язык с оригиналом изучены основные методы, применяемые
при передаче социолингвистических особенностей исходного текста на язык перевода. В статье
приводятся примеры перевода французских реалий, социальных явлений, говорящих фамилий. Стаття розкриває характерні риси літератури постмодернізму, дає характеристику
складнощів, які можуть виникнути при перекладі соціолінгвістичного аспекту мови і причини їх
виникнення. За допомогою порівняльного аналізу перекладу роману Мішеля Уельбека «La carte et le
territorie» на російську мову з оригіналом вивчені основні методи, які застосовуються при передачі
соціолінгвістичних особливостей вихідного тексту на мову перекладу. У статті наводяться приклади
перекладу реалій французької культури, соціальних явищ, прізвищ. The article reveals the characteristic features of literature of the postmodernism, gives a description
of problems that may arise within the process of translation of the sociolinguistic aspect of the language and
their causes. Due to the comparative analysis of the translation of the novel by Michel Houellebecq «La carte et
le territorie» into Russian with its original in French were studied the main methods used in the transmission of
sociolinguistic features of the source text into the target language. The article gives examples of the translation
of French realia, social phenomena and names.
In most cases to find an appropriate equivalent for transmission of a particular realia is almost impossible.
That’s why usually a translator has to do the transcript of the word and make special notes to explain a
phenomenon of the culture to not native-speaking readers. Unfortunately the huge majority of notes in texts of
translation don’t let the reader to feel the particular author’s style that’s why new ways of translation should be
studied and provided in the process of realia’ translation. In the long term research there’s a study of
translation of other novels by this author, as well as translation of novels other postmodernists in order to build
a common model of the transmission of sociolinguistic aspects from the source language into the target
language with minimal stylistic and structural losses.